Engineering geology and geological engineering for sustainable use of the Earth's resources, urbanization and infrastructure protection from geohazards : proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures /: proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures. ([2018]) - Unknown
No abstract available